Incidence of potato green aphid and Liriomyza sp. in radish plants grown on different levels of organic fertilizer - Borges, Vinicius; de Souza Lemos Neto, Hozano; Melo, Jose Wagner da Silva; Guimarães, Marcelo Almeida (EntomoBrasilis, 2021)
Radish is a short cycle horticultural product from family Brassicaceae. Between the insects found on radish leaves, potato green aphid (Myzus persicae Sulzer) is one of the main pests of this culture, causing economic damage. Synthetic fertilizers used in conventional crops can promote changes in the pattern of amino acids in plants, leading to a higher insect damage. The source of fertilization is one of the factors that could influence in the incidence of pests. The objective of the study was to evaluate the incidence of potato green aphid and other pests on radish plants grown with different doses of organic fertilizer. The experiment was carried under semi-field conditions, in Fortaleza (Ceará State). A completely randomized design was used, with six replicates. The treatments consisted of five doses of organic compost (0; 45; 60; 75; 90 t.ha-1). For the population survey of pests and natural enemies, counts were made in three evaluations (7, 14 and 21 days after sowing). The counting data were subjected to deviance analysis using a generalized linear model (GLM). It was observed significant differences in the number of adults M. persicae in the treatments of 75 and 90 t.ha-1. Presence of leafminer (Liriomyza sp.) was observed on plants without and with the lower doses of organic fertilizer. Even using organic fertilizers that promote a slower liberation of nutrients, high incidence of pests (Mainly M. persicae) was observed on radish plants.